Experimental study of the efficiency of gas chromatographic methods for determination of volatile compounds in alcohol products - Sabalenka, Lidziya N.; Charapitsa, Siarhei V.; Sytova, Svetlana N.; Kavalenka, Anton N.; Yushkevitch, Daniil V.; Zajats, Mikhail F.; Egorov, Vladimir V.; Leschev, Sergey M.; Melsitava, Ina V. (Journal of the Belarusian State University. Chemistry, 2023)
The results of an experimental study of the efficiency of external and internal standard methods for the analysis of alcohol products based on the chromatographic separation of 10 volatile compounds on a capillary column and their following detection with a flame ionisation detector are presented. Based on the experimental data obtained for the external standard method, traditional and modified internal standard methods their main metrological characteristics: limits of detection, limits of quantification, linearity, repeatability, intermediate precision, and correctness of results were calculated. Methods were compared on 25 matrices of alcohol products with a volume fraction of ethanol in the range of 6.5 to 70.0 %.
Keywords: alcoholic products; gas chromatography; internal standard; external standard